2022
DOI: 10.1016/j.aace.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Co-Transporter Protein 2 Inhibitors Induced Hypercalcemia: A Case Series and Literature Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Case reports have documented reversible hypercalcemia with sodium-glucose cotransporter protein 2 inhibitors, likely due to osmotic diuresis and volume contraction. Underlying risk factors (dehydration, high calcium intake, thiazides, acidosis, undiagnosed PHPT) were typically present . Estimates of the frequency are not available, but a meta-analysis of 25 RCTs indicated that the increase in serum calcium was not consistent with a meaningful change .…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Case reports have documented reversible hypercalcemia with sodium-glucose cotransporter protein 2 inhibitors, likely due to osmotic diuresis and volume contraction. Underlying risk factors (dehydration, high calcium intake, thiazides, acidosis, undiagnosed PHPT) were typically present . Estimates of the frequency are not available, but a meta-analysis of 25 RCTs indicated that the increase in serum calcium was not consistent with a meaningful change .…”
Section: Observations and Discussionmentioning
confidence: 99%
“…To our knowledge, only three papers reviewed this subject in the available literature written in the English language. All of them are case reports and case series, with a total of five patients [ 2 ]. We present herein a case of primary hyperparathyroidism masked by the use of empagliflozin.…”
Section: Introductionmentioning
confidence: 99%